Voltammetry on mercury and carbon electrodes as a tool for studies of metallothionein interactions with metal ions - Sestáková, I; Mader, P (Cellular and molecular biology (Noisy-le-Grand, France), 2000)
Rabbit liver Cd-metallothionein (CdMT) and Cd-complex of synthetically prepared pentapeptide (gamma-Glu-Cys)2-Gly were studied as examples of animal and plant metallothioneins. Using hanging mercury electrode, cathodic stripping voltammetry after adsorptive accumulation of the Cd(II)-SR complex at different potentials, is suitable for estimating changes occurring in metal coordination due to the presence of metal ions such as Zn2+, Cu2+, Hg2+ or excessive Cd2+. Conditions under which similar behaviour can be observed for both CdMT and Cd-pentapeptide complex are specified. On carbon electrodes, detailed study of reduction processes of Cd(II)-SR complexes is prevented by occurrence of a large catalytic current; oxidation processes are more suitable for study at these electrodes. Carbon composite paste electrode (10% SiO2) allows deposition of Cd(II)-SR complex during its reduction, as was demonstrated with Cd-cysteine, CdMT or Cd-pentapeptide complex. After deposition, oxidation peak of the uncomplexed Cd2+ ions and one or two oxidation peaks corresponding to a formation of the RS-Cd(II) complex are observed. Also, similarly as on Hg electrode, it was observed that excessive Cd2+ or Zn2+ ions influence oxidation peaks of the RS-Cd(II) complex formation. Combination of measurements on mercury electrode and composite paste electrode is recommended for studies of metallothionein interactions with metal ions or other metal complexes.
Keywords: kadmium; Metallothionein; elektrochemie; Hydrogen-Ion Concentration; uhlík; cystein; Cysteine; Carbon; Mercury; rtuť; zinek; Glutamine; králíci; ionty; glutamin; Electrochemistry; Zinc; elektrody; Peptides; zvířata; játra; peptidy; Liver; Ions; Animals; Rabbits; Electrodes; koncentrace vodíkových iontů; metalothionein; Cadmium